AL-QUR’AN TRANSLITERASI LATIN DAN PROBLEMATIKANYA DALAM MASYARAKAT MUSLIM DENPASAR - Musadad, Muhammad (Lajnah Pentashihan Mushaf Al-Qur'an, 2017)
Transliteration of the Qur'an appears as an alternative for some people who are unable to read the Qur'an in Arabic script. The users of transliteration of the Qur'an in the city of Denpasar are from the new converts and mature as well as old age. This research shows that the guidance of translation from the Minister of Religious Affairs, Minister of Education and Culture in 1987 as well as guidelines of transliteration of tajwÃ„Â«d (the art of reciting the QurÃ¢â‚¬â„¢an) is not well socialized. Practically, the users do not quite understand some of the transliteration symbols. Factors behind the use of transliteration of the Qur'an is because from the early childhood to adolescence they do not get enough education in Qur'anic teaching. Another factor is the lack of support from the family regarding the importance of learning the Qur'an. As for the problem faced by the users is minimum ability of the basic knowledge of Arabic alphabets (hijÃ„ÂÃ¢â‚¬â„¢iyah) that makes them difficult to implement the synonyms of the Arabic alphabets to the Latin ones. The intensity to read the Qur'an was also minimum, thus inhibiting the smoothness in reading transliteration of the Qur'an. Keywords Transliteration of the Qur'an, reading the Qur'an, muslim of Denpasar.